New Record of Lycodon liuchengchaoi in Anhui - Zhang, Liang; Peng, Li-Fang; Yu, Lei; Wang, Zheng-Ping; Huang, Li-Qun; Huang, Song (Dōngwùxué yánjiū, 2015)
One juvenile and one adult female wolf snake（Colubridae： Lycodon） were sampled at Yixian and Fuxi, Huangshan, Anhui, China in the summer of 2011 and 2012, respectively. The two specimens were identified as Lycodon liuchengchaoi based on external morphology and molecular data. This is a new reptile record in Anhui Province. In our laboratory, four eggs were laid and three neonates were hatched successfully. This is the first record of the laying and incubation of L. liuchengchaoi eggs. The five specimens were deposited at the Museum of Huangshan University（HUM20140001） and Guangdong Entomological Institute（HB-lcfsp12613, HB-lcfsp-ch1~3）.